Changing practices due to a shortage of nurses: A qualitative exploratory study - Mia Ingerslev Loft; Stina Marlo Posborg; Lone Lundbak Mathiesen; Sidsel Goor Pedersen; Maria Brudsø; Rie Forsberg; Thomas Sellberg Nielsen; Christian Gybel Jensen (International Journal of Nursing Studies Advances)
Background: Nurses have a vital role in the care and treatment of patients. According to the World Health Organization, there is a shortage of nurses. Low nurse recruitment has led to new forms of task shifting, where other professionals are hired to take over specific tasks traditionally performed by nurses, their purpose being to relieve nurses to deal with other essential tasks. Objective: The aim of this study was to explore the experiences and attitudes of nurses towards other professionals taking over traditional nursing tasks. Design: This study utilised a qualitative explorative research design with a hermeneutic approach. We conducted semi-structured interviews. Setting: Nurses were recruited from a hospital over two locations in the Capital Region of Denmark. The nurses were from six different neurological units, representing acute neurological inpatient settings, inpatient rehabilitation, and an outpatient setting. Participants: The study included 27 participants; clinical nurses, nurse specialists and nurse managers. Methods: Our study was based on a hermeneutic approach. We used an interview guide that drew on the existing literature, background knowledge and known gaps to explore. All interviews were audio-recorded and transcribed. The text was analysed using qualitative content analysis. Results: The analysis provided insights into how nurses experience the trend of other professionals taking over traditional nursing tasks. This was described through 5 different categories and one overall theme; Becoming a nurse, To help and care for someone in need - what nursing is about, A necessity caused by the nurse shortage, Changes in workflows and tasks – support and uncertainty, Organising and implementing changes, Home of the nurses – a complex whole. Conclusions: The nurses’ experiences and attitudes towards other professionals as they took over traditional nursing tasks were complex and multifaceted. The changes happening in the nursing practice, were seen by nurses as a forced but accepted helpful necessity to relieve them in their everyday work and contribute with specialised knowledge, to the field of nursing. Still, the effects of changes were limited by the complexity of tasks, workflows and structures within the practice, and by present ideals of what professional nursing is and should strive to be. Nurses are essential to include when deciding which professions to include, and how it can be done effectively, but it is just as important to include perspectives of new potential professionals both in research and when making decisions for the future. Tweetable abstract: Changing practices caused by the nursing shortage – Exploring new forms of task shifting from the perspective of nurses.